Natural polymorphisms of HIV type 2 pol sequences from drug-naive individuals - Parreira, R. (2013)
Until today, the susceptibility of human immunodeficiency virus type 2 (HIV-2) to protease and nucleosidic reverse-transcriptase inhibitors (PI and NRTI, respectively) has not been clearly documented. In this report we studied HIV-2 proviral sequences (n = 30) from drug-naive patients. Our results revealed that several amino acid positions in the protease and reverse transcriptase coding sequence harbored residues that have been associated with drug resistance in HIV-1-infected patients. In particular, the M46I substitution in the protease was detected in 90% of the sequences analyzed, which, together with the other substitutions identified, may indicate a reduced susceptibility of HIV-2-infected drug-naive patients to PI. Furthermore, interpretation of genotypic data with four available algorithms, developed for interpretation of HIV-1 sequence data, suggested nonoverlapping profiles of drug resistance.